2021
DOI: 10.1177/00207640211011365
|View full text |Cite
|
Sign up to set email alerts
|

Suicide deaths among medical students, residents and physicians in India spanning a decade (2010–2019): An exploratory study using on line news portals and Google database

Abstract: Background: Despite having one of the world’s largest medical education consortium, India lacks a comprehensive and nationally representative data on suicide deaths among medical students and physicians unlike the one found in most of the developed nations of the world. Aim: We aimed to explore the different characteristics of suicide deaths among medical students, residents and physicians in India over a decade (2010–2019). Methods: Content analysis of all suicide death reports among medical students, residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…In an Indian study by Chahal et al, evaluating 358 deaths among HCPs between 2010–2019, it was found that violent suicide methods were more commonly used, with hanging being the most common means of suicide [ 12 ]. Kishore et al explored 30 reported suicides by Indian doctors between the years 2013–2016 and found that 17 doctors (57%) resorted to hanging, 8 (26%) used lethal injections, 5 (17%) jumped from a building, and one jumped in front of a train [ 5 ].…”
Section: Methods Used For Suicidementioning
confidence: 99%
See 2 more Smart Citations
“…In an Indian study by Chahal et al, evaluating 358 deaths among HCPs between 2010–2019, it was found that violent suicide methods were more commonly used, with hanging being the most common means of suicide [ 12 ]. Kishore et al explored 30 reported suicides by Indian doctors between the years 2013–2016 and found that 17 doctors (57%) resorted to hanging, 8 (26%) used lethal injections, 5 (17%) jumped from a building, and one jumped in front of a train [ 5 ].…”
Section: Methods Used For Suicidementioning
confidence: 99%
“…Workplace harassment in the form of ragging, discrimination and nepotism has also led to suicides among medical and nursing students and resident trainees. Personal life problems such as marital discord/relationship issues are also some of the prominent causes of suicide among physicians [ 12 ].…”
Section: Methods Used For Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Chahal et al . [ 4 ] explored suicidal deaths among medical professionals between 2010 and 2019 based on news reports and found that 358 deaths by suicide in 10 years, 70% of which occurred before the age of 30 years and 26% of which had shown warning signs prior to the act. Another Indian study reported 30 suicidal deaths between 2016 and 2019, 80% of which occurred in those younger than 40 years.…”
mentioning
confidence: 99%
“…[ 4 ] A recent study from India found that 358 deaths due to suicide were reported among medical students (125), residents (105), and physicians (128) between 2010 and 2019. [ 5 ] A recent study from the United States of America calculated a prevalence of 6.19 suicides/100,000 students during a period of 10 years. [ 6 ] Medical students and physicians too are not exempt from stigma associated with mental health problems.…”
mentioning
confidence: 99%